URGENSI TRANSFORMASI DIGITALISASI PERBANKAN SYARIAH SECARA MASIF DALAM KERANGKA MAQASHID SYARIAH - Anggreni, Melisa; Taufiq, Muhammad (Pusat Riset dan Inovasi Nasional, 2022)
The growth of the sharia bank business has been predicted to exceed the growth of the national banking sector as disclosed by the Chief Economist of PT Bank Syariah Indonesia Tbk (BSI) Banjaran Surya Indrastomo in the BSI Sharia Outlook 2023. However, the increase in Third Party Funds (DPK) was 11.46% YoY or higher than the national banking DPK projection of 9.6% YoY does not automatically increase the overall interest of sharia banking customers in choosing sharia banking services compared to conventional banking services. We can see this from the data on the number of placements of government funds, both BUMN, BUMD & Public Service Agencies (BLU), including the UIN Sjech M. Djamil Dajmbek Bukittinggi work unit, which are more in conventional banks than Islamic banks. Data on users of Islamic bank services and conventional banks at UIN Sjech M. Djamil Djambek Bukittinggi also have more conventional bank service users than Islamic banks with a ratio of 60% to 40%, based on data from 252 employees of the State Civil Apparatus of UIN Bukittinggi, only 106 service users. Islamic banks that place payroll or salary funds in Islamic banks and the rest use conventional banks. This phenomenon is the basis for the analysis in this study where from interview surveys with some employees of the State Civil Apparatus of UIN Bukittinggi where Islamic bank digital banking is one of the indicators driving interest in using Islamic bank services. Qualified digital banking is a must and must be able to accommodate the interests of Islamic banking services to achieve the goal of benefit within the framework of Maqashid Syariah (Dharuriyyah, Hajiyat and Tahsiniyat). The division of dharuriyyah is categorized into 5 basics, namely 1) Religion, 2) Soul, 3) Heredity, 4) Intellect and 5) Wealth. This research method uses a qualitative research study with a literature review approach. The results of the study show that digital transformation in an inclusive manner is an urgency that cannot be postponed anymore and must be carried out massively by increasing the capacity of Islamic banking capital in the IT sector of Islamic banking.